Social matter, social design : Jan Boelen; Michael Kaethler (eds.) - Boelen, Jan; Keathler, Michael (Amsterdam : Valiz, 2020)
Deconstructing social norms in and through sport / Gabriel Fontana -- Public toilets for women / Elisa Otañez -- Wonderment domastication / Gabriel A. Maher -- How a tiger penis became a design problem / Kuang-Yi Ku -- The self as other / Vera Sacchetti -- Genesis / Marianne Drews -- Bricks / Ellie Birkhead -- Re-mining / Noud Sleumer -- Everyday resilience / Mariangela Beccoi -- The horseshoe theory / Vivien Tauchmann -- How I learned to stop worrying and love the Iron Dome / Gali Blay -- The Russian Parmesan paradox / Anastasia Eggers -- The design of waste / Nadine Botha -- Over the southernmost border of social design, trees are people too / Pablo Calderón Salazar -- From common space to private sphere / Saba Golchehr -- Burner phones / Søren Rosenbak -- Missing darkness / Angela Rui -- From the poverty of desire to the rebirth of creativity / Ottonie von Roeder -- The future of technology will be humanist / Henrique Nascimento -- A centaur orientation / Alorah Harman -- A machine monologue / Jonas Althaus -- Doubts and dilemmas / Michael Kaethler with Dick van Hoff, Brecht Duijf, Henriette Waal, Eric Klarenbeek, and Stéphane Barbier Bouvet -- All design is social / Michael Kaethler.
boek